Integrasi Perdagangan dan Keselarasan Siklus Bisnis di ASEAN - Hervino, Aloysius Deno (Jurnal Ekonomi Kuantitatif Terapan, 2020)
This research aims to analyze the impact of trade integration in term of demand spillover (export, import, and both) on business cycle co-movement which measured by Gross Domestic Product Real. Using data from World Integrated Trade Solution (WITS) and Fixed Effect Model (FEM), the results of this research explain that trade integration from import side among ASEAN countries has a positive impact on business cycle co-movement, but from export-side the impact is negative. Otherwise, this research didn’t found a significant impact from both export and import side to business cycle co-movement among ASEAN member countries.